Studying the Collection of Varietal Samples of Khandalyak Melons - Ballasov, A. R.; Usmanova, B. M. (American Journal of Botany and Bioengineering, 2024)
The scientific article examines samples and hybrids of khandalak melon imported from abroad, compares them with local varieties, how they differ from each other, resistance to diseases, adverse external factors, growing period and yields on farms. Based on the results of the research, we can say that Obinovvot bonka, Handalak pochka, Handalak 5000, Big yellow khandalak, Early ripening small khandalak are high-yielding, i.e. 60-70 percent above standard.